EVALUATION OF VARIOUS FILTERS IN RECIRCULATION AQUACULTURE SYSTEMS ON SURVIVAL RATE, CORTISOL, GROWTH AND OSMOTIC PERFORMANCE IN CHANNA MARULIOIDES AS DOMESTICATION EFFORT - Rizal. A. Hutagalung; S. Anggoro; Suryanti Suryanti; M. R. Muskananfola (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study aims to determine the effectiveness of various filter materials in RAS such as synthetic materials and organic materials and there an impact on plasma cortisol, osmotic performance rate, growth rate and survival rate of Channa marulioides. The cultivation process in the RAS system is carried out for 100 days with 50 individuals in each different treatment, namely T1: Synthetic filter; T2: Organic filter; T3: Mixture of synthetic and organic filter; Control: No Filter and RAS. Measurements of plasma cortisol and osmotic performance levels were carried out at the beginning and end of cultivation which had an impact on growth and survival rates. The results of the study showed a decrease in cortisol levels (ng/ml), namely: T1: 9.24, T2: 9.66, T3: 10.37 which showed that there was no significant difference in each treatment (P> 0.05) but in T1, T2, and T3 were significantly different with control treatment: 1.32 (P